2021
DOI: 10.1016/j.eclinm.2020.100715
|View full text |Cite
|
Sign up to set email alerts
|

The metformin in tuberous sclerosis (MiTS) study: A randomised double-blind placebo-controlled trial

Abstract: Please cite this article as: S. Amin et al., The metformin in tuberous sclerosis (MiTS) study: A randomised double-blind placebo-controlled trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…One trial involved 12 patients with Lafora disease who were treated with metformin and were found to experience a slower progression of the disease [ 25 ]. The second trial was a multicentre, randomised, double-blind, placebo-controlled clinical trial of metformin in the treatment of tuberous sclerosis, which found that metformin reduced seizure frequency compared with the placebo [ 26 ]. From a clinical practice perspective, the present findings, together with previous randomised controlled trials, provide some support for the potential therapeutic role of metformin in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…One trial involved 12 patients with Lafora disease who were treated with metformin and were found to experience a slower progression of the disease [ 25 ]. The second trial was a multicentre, randomised, double-blind, placebo-controlled clinical trial of metformin in the treatment of tuberous sclerosis, which found that metformin reduced seizure frequency compared with the placebo [ 26 ]. From a clinical practice perspective, the present findings, together with previous randomised controlled trials, provide some support for the potential therapeutic role of metformin in patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach might even allow employing a less strict dietary protocol. Metformin may be a primary candidate for this, since it has recently demonstrated clinical activity in the model brain tumors driven by the metabolic master regulator mTOR in tuberous sclerosis patients [ 43 ]. Synergistic effects may also be expected by combination with inhibitors of glycolysis like WP1122 [ 44 ] or by blocking glutamine metabolism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pretreatment with metformin reduced inflammatory cytokines and increased the neuroprotective progranulin and anti‐inflammatory cytokines in rats with experimental temporal lobe epilepsy 43 . A randomized clinical trial revealed that metformin reduced epileptic seizure frequency in children with tuberous sclerosis 44 . In addition, metformin is effective against Lafora disease which is a progressive form of myoclonic epilepsy due to a mutation in the EPM2A gene 45 .…”
Section: Metformin and Epilepsymentioning
confidence: 99%
“… 43 A randomized clinical trial revealed that metformin reduced epileptic seizure frequency in children with tuberous sclerosis. 44 In addition, metformin is effective against Lafora disease which is a progressive form of myoclonic epilepsy due to a mutation in the EPM2A gene. 45 A cohort study involved 18 patients with Lafora disease, 8 treated with metformin and 10 untreated showed that metformin was effective in reducing epileptic seizure severity and frequency.…”
Section: Metformin and Epilepsymentioning
confidence: 99%